Differences in Alcohol Consumption Duration on Cholesterol Levels - Nuroini, Fitri; Agustin, Dela Putri; Isworo, Joko Teguh; Sukeksi, Andri (Prosiding Seminar Kesehatan Masyarakat [Proceeding of Public Health Seminar], 2024)
Background: Alcohol is toxic containing hydrophilic ethanol so that it easily enters the body which will be converted into acetaldehyde by aldehyde dehydrogenase (ALDH) and oxidized to acetate. Excessive acetate is converted into acetyl-CoA which is converted into fatty acids that will continue to accumulate to increase cholesterol. Consuming alcohol within 5 years with a frequency of 3-4x per week can increase cholesterol levels. The study aimed to determine the difference in the duration of alcohol consumption (≤ 5 and > 5 years) on cholesterol levels. Method: Analytic observational research with a cross-sectional approach. Samples were taken randomly from as many as 20 people who consumed alcohol ≤ 5 and > 5 years at a cafe in Salatiga. Cholesterol levels were examined using the POCT method, and then cholesterol levels were statistically analyzed using Shapiro Wil and Independent T-Test. Result: The mean cholesterol levels of respondents who consumed alcohol ≤ 5 and > 5 years were 172.30 ± 16.63 mg/dL and 236.80 ± 34.74 mg/dL, respectively. Cholesterol levels of respondents who consume alcohol ≤ 5 are still in the normal category while cholesterol levels of respondents who consume > 5 years fall into the high-risk category. Based on the statistical results, it is known that the data is normally distributed and there are differences between respondents who consume alcohol ≤ 5 years and > 5 years. Conclusion: The cholesterol levels of respondents who consumed alcohol > 5 years were higher than those who consumed alcohol ≤ 5 years.